Asymmetric cross‐border protection of peripheral transboundary species. Issue 3 (18th December 2017) - Thornton, Daniel H.; Wirsing, Aaron J.; Lopez‐Gonzalez, Carlos; Squires, John R.; Fisher, Scott; Larsen, Karl W.; Peatt, Alan; Scrafford, Matt A.; Moen, Ron A.; Scully, Arthur E.; King, Travis W.; Murray, Dennis L.
Abstract: International political boundaries challenge species conservation because they can hinder coordinated management. Peripheral transboundary species, those with a large portion of their range in one country and a small, peripheral portion in an adjacent country, may be particularly vulnerable to mismatches in management because peripheral populations are likely in greater conservation need than core populations. However, no systematic assessment of peripheral transboundary species or their status across borders has been attempted. We show that numerous species in three vertebrate taxa qualify as peripheral transboundary species in North America, and that these species are often protected differently across US–Canadian and US–Mexican borders. Asymmetries in cross‐border protection may threaten populations through disruption of connectivity between periphery and core regions and are especially relevant given expected impacts of climate change and the US–Mexico border wall. Our results highlight the need for greater international collaboration in management and planning decisions for transboundary species.